2011
DOI: 10.1016/j.jvs.2011.06.114
|View full text |Cite
|
Sign up to set email alerts
|

Long-term single institution comparison of endovascular aneurysm repair and open aortic aneurysm repair

Abstract: EVAR requires more late secondary vascular interventions than open AAA repair, but patients who undergo open repair have more nonvascular long-term morbidity. Long-term survival is better after EVAR compared to open repair in this selected patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…12 Other groups have reported reintervention rates between 12% and 27%. 2124 In larger series, reintervention rates were also comparable: Lifeline, 18% at 5 years; OVER, 14% at 1.8 years; and EVAR1, 23% at 5 years. 4,8,25 The increased ARM seen in the reintervention subgroup and the delayed nature of many of these procedures serves to underscore the need for long-term surveillance.…”
Section: Discussionmentioning
confidence: 87%
“…12 Other groups have reported reintervention rates between 12% and 27%. 2124 In larger series, reintervention rates were also comparable: Lifeline, 18% at 5 years; OVER, 14% at 1.8 years; and EVAR1, 23% at 5 years. 4,8,25 The increased ARM seen in the reintervention subgroup and the delayed nature of many of these procedures serves to underscore the need for long-term surveillance.…”
Section: Discussionmentioning
confidence: 87%
“…A total of 29 papers were read in full. Eighteen studies were excluded for the following reasons: two were meta‐analyses, two were RCTs with fewer than 200 patients, six non‐randomized studies had fewer than 2000 patients, one study investigated challenging aortic necks, one investigated aortoiliac aneurysms, two investigated high‐risk patients, one was a prospective non‐randomized trial with fewer than 2000 patients, one was a systematic review, one included only patients aged more than 80 years, and one excluded patients aged over 60 years ( Fig . ).…”
Section: Resultsmentioning
confidence: 99%
“…1316 . Moreover, it has been shown that a substantial proportion of AAA patients later require non-aortic vascular surgery, 17 which will likely increase as life expectancy is improving. By sparing a second operation, total morbidity, hospitalization and costs may decline.…”
Section: Introductionmentioning
confidence: 99%